Accidental identification of accessory mental nerve and foramen during implant surgery - Kulkarni, Sudhindra (Medknow Publications, 2011)
The accessory mental nerve and the corresponding foramen are not a very common occurrence. In the current case report, we present the notice of an accessory mental nerve in the mandibular molar area during implant placement. The case was managed well without any complications.